The Role Of Bhabinkamtibmas (Neighborhood/Village Police Ncos) And Community Empowerment In East Banjarmasin: The Analysis Of Constraints And Community Development - Haris Haris; Ahmad Alim Bachri; Muhammad Riduansyah Syafari (Wadah Inovasi Indonesia, 2021)
The National Police of the Republic of Indonesia, in this case, Bhabinkamtibmas (Neighborhood/Village Police NCOs), as the leader in creating Harkamtibmas or the maintenance of security and public order in villages/sub-districts, can carry out their duties by applying the community empowerment as an effective way to involve the community in achieving all goals and hopes of creating a safe and orderly situation where they are being assigned. This had been stated in the Regulation of the Chief of the Indonesian National Police Number 3 of 2015 article 27 that the main task of Bhabinkamtibmas is to conduct community development, early detection, and mediation/negotiation to create conducive conditions in the village/sub-district. In regards to community policing in Article 1 Paragraph 2, community policing, from now on abbreviated as Polmas, is an activity to invite the public through a partnership between members of the National Police and the community, so that they can detect and identify problems of security and public order (Kamtibmas) in their environment and resolve them. The results of the research showed that community empowerment in East Banjarmasin could be carried out through the role of Bhabinkamtibmas. However, it was not optimal because many programs or activities executed by Bhabinkamtibmas were reserved to fulfilling tasks that had been assigned to them. The community empowerment was followed through practically and was limited to how to take advantage of the situation and part of the community's potential in order to finish the target assigned to them hence the role of Bhabinkamtibmas as the leader in community empowerment could not be implemented properly and sustainably. The achievement could be done through the provision of knowledge and training and education on understanding the definition of community empowerment as a process and as a goal, stages of empowerment, empowerment strategies and so on, in order to create a community in which they are ready to be efficient and independent towards creating a conducive security and public order therefore they can create a safe, peaceful community and ensure the implementation of development towards prosperity.